Contraceptive continuation among women aged 15-49 utilizing City of Cape Town family planning services - Naidoo, Carron (Department of Public Health and Family Medicine, 2024)
There is a need to provide comprehensive contraceptive services that are consistent and that address the requirements of women, particularly young women who are at risk of unintended pregnancy. Objectives This study describes characteristics of contraceptive users accessing services and their contraceptive method usage patterns, including continuation, at public sector clinics in Cape Town, South Africa. Methods The study reviewed data on contraceptive users (n=217 274), aged 15-49 years accessing services across 102 public sector clinics. We calculated all method continuation and method-specific continuation for all hormonal methods. Multi-variate analysis was used to examine the relationship between sociodemographic and health characteristics with contraceptive continuation. P-values <0.05 were considered significant. Results Of the 217 274 women, 95.6% used short acting methods (68.2% injectables, 9.1% oral pills, 18.2% male & female condoms), while <5% used long-acting methods (implant 3.9%, intrauterine device 0.4%). The proportion of all method continuation was 39.5%, but the norethisterone enanthate injectable had the lowest method-specific continuation at 8%, followed by the oral pill at 11%, the two most popular contraceptive methods used by younger women. Contraceptive continuation was strongly associated with dual method use (OR: 1.78; 95% CI: 1.74-1.84), older age (25-49) (OR: 1.16; 95% CI:1.13-1.18) and had reduced odds if a user was on treatment for TB (OR: 0.64; 0.57-0.73). Conclusions Both method-specific and all-method contraceptive continuation were low, which indicates high rates of contraceptive method discontinuation without women switching their method. This may point to issues requiring attention at health provider, health system and client levels. Expanding patient- centered counselling and education, ongoing in-service education of health providers, and inventory monitoring systems to address issues such as stockouts are needed.